2017
DOI: 10.3329/jemc.v7i3.34072
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Aetiology and Antibiotic Resistance Pattern of Community-Acquired Urinary Tract Infections in Children in a Tertiary Care Hospital in Bangladesh

Abstract: Background: Urinary tract infections (UTIs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…(Table 5). [59][60][61][62][63][64]. The low sensitivity of leucocyte esterase test could have been due to the low concentration of pyuria in majority of the study participants; similarly the low sensitivity of the nitrite observed in this study may have been due to the use of random urine specimen for analysis as long bladder incubation period is required for conversion of dietary nitrates to nitrites.…”
Section: Diagnostic Value Of Urinalysis In Urinary Tract Infection Am...mentioning
confidence: 99%
“…(Table 5). [59][60][61][62][63][64]. The low sensitivity of leucocyte esterase test could have been due to the low concentration of pyuria in majority of the study participants; similarly the low sensitivity of the nitrite observed in this study may have been due to the use of random urine specimen for analysis as long bladder incubation period is required for conversion of dietary nitrates to nitrites.…”
Section: Diagnostic Value Of Urinalysis In Urinary Tract Infection Am...mentioning
confidence: 99%